Circadian glucocorticoids throughout development - Lehmann, Marianne; Haury, Katharina; Oster, Henrik; Astiz, Mariana (Frontiers in Neuroscience, 2023)
Glucocorticoids (GCs) are essential drivers of mammalian tissue growth and maturation during one of the most critical developmental windows, the perinatal period. The developing circadian clock is shaped by maternal GCs. GC deficits, excess, or exposure at the wrong time of day leads to persisting effects later in life. During adulthood, GCs are one of the main hormonal outputs of the circadian system, peaking at the beginning of the active phase (i.e., the morning in humans and the evening in nocturnal rodents) and contributing to the coordination of complex functions such as energy metabolism and behavior, across the day. Our article discusses the current knowledge on the development of the circadian system with a focus on the role of GC rhythm. We explore the bidirectional interaction between GCs and clocks at the molecular and systemic levels, discuss the evidence of GC influence on the master clock in the suprachiasmatic nuclei (SCN) of the hypothalamus during development and in the adult system.